HUBUNGAN BEBERAPA FAKTOR DENGAN KURANGNYA PENGGUNAAN METODE KONTRASEPSI JANGKA PANJANG PADA IBU USIA 15 – 49 TAHUN DI PROVINSI MALUKU UTARA (ANALISA DATA SDKI 2017) - Ternate, Elvicta Venteysa; Nugroho, Raden Djoko; Wirnani, Sri; Purnami, Cahya Tri (Jurnal Kesehatan Masyarakat (Undip), 2021)
Long Term Contraceptive Method (MKJP) is the most effective contraceptive method in reducing the number of birth rates. In 2012 the prevalence of MKJP of North Maluku Province (23.7%) prevalence of MKJP usage below the national figure (27.5%). This study aims to analyze factors related to the practice of mkjp use in mothers aged 15-49 years in North Maluku Province. This type of research is explanatory research using Cross Sectional design. This study has a population of 316,855 mothers 15 - 49 years, a sample of 1050 mothers who use contraceptives Data sources in this study are the results of the 2017 Indonesian health demographic survey (SDKI). This type of research is quantitative research Stages conducted in data processing are data input, edit, and clening., entry, tabulation. Analysis is done based on univariate (frequency distribution) and bivariate (frequency distribution, cha square, and p-value= 0.05.) The results showed that most mothers who did not use MKJP (81.2%), mothers aged <35 years (61.5%), mothers with the number of children living 0 - 2 (64.6%), mothers with low levels of pedidikan (79.2%), mothers of poor knowledge about the type of contraceptives (54%). Sources of birth control services received by mothers as much as (53.2%) from other sources of service (friends, shops, NGOs). The practice of using MKJP relates to maternal knowledge (p-value = 0.050), maternal education level (p-value = 0.002), the area where the mother lives (p-value = 0.000), and the source of maternal kb services (p-value = 0.018). However, the age of the mother (p- value = 0.436) and the number of children living in the mother (p-value = 0.106) have no relationship with the practice of using MKJP in mothers.Keywords: Long-Term Contraceptive Method, Lifespan, number of children living, knowledge, education level, residential area, source of birth control services.